2019
DOI: 10.1186/s12903-019-0858-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of an interdental brush mitigates periodontal health inequalities: the Korean National Health and nutrition examination survey (KNHANES)

Abstract: Background The purpose of this study was to evaluate the mitigating effect of the use of interdental brushes on periodontal health inequality. Methods This study was based on the data acquired in the Sixth Korea National Health and Nutrition Examination Survey (KNHANES VI; 2013–2015). A total of 17,583 participants (7,633 males and 9,950 females)) aged 19 years or older completed the KNHANES VI between 2013 and 2015. Multivariable logistic regression analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
14
1
3
Order By: Relevance
“…The use of interdental brush was also found to be encouraging at 65%. This is very high compared to other studies, whereby their studies reported 6.9% and 20.4% of their respondents with interdental brush usage, respectively (Badiah, 2015;Lee et al, 2019). This can be due to the advice given on interdental brush instead of floss, as more spacing between teeth can be found in periodontitis cases.…”
Section: Discussionmentioning
confidence: 69%
“…The use of interdental brush was also found to be encouraging at 65%. This is very high compared to other studies, whereby their studies reported 6.9% and 20.4% of their respondents with interdental brush usage, respectively (Badiah, 2015;Lee et al, 2019). This can be due to the advice given on interdental brush instead of floss, as more spacing between teeth can be found in periodontitis cases.…”
Section: Discussionmentioning
confidence: 69%
“…A systematic review suggested that interdental cleansing, such as the use of an interdental brush, should be performed in parallel rather than in isolation as an effective means of reducing periodontal disease and plaque index [44]. This procedure also revealed the effects of alleviating periodontal health inequalities and is an important tool for maintaining oral health [45]. This study clari ed that these oral health states and behaviors are related to each other and exhibited similar tendencies to those reported previously ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The covariates of this study were the following major sociodemographic factors: sex, age, household income, and education [13]. Household income was classified as <25% (the lowest quartile group), 25-49%, 50-74%, and 75-100% (the highest quartile group).…”
Section: Covariatesmentioning
confidence: 99%